“There is Nothing There.” Dmitrii Danilov’s Travel Writing and the Lure of the Russian Provinces (ENTHYMEMA, 2022)
Drawing on Michel de Certeau’s seminal study The Practice of Everyday Life, the author argues that Dmitrii Danilov’s travel writing (Twenty Cities, 2007-2009) reimagines Russia’s symbolic geography by destabilizing the traditional opposition centre – periphery. Rather than depicting the provincial world as either an absurd and horrid world, or as a repository of “true Russianness”, Danilov provides a “decentred” perspective on the provinces that asserts the uniqueness of each city he visits. The novel Description of a City (2012), however, resurrects the more traditional view of the provinces as a world of boredom and cultural lack. To analyse this development the article looks at the central figure of the sluggish traveller-narrator, the employment of “camera-eye narration” and other, mainly linguistic, devices that reaffirm the notion of the provincial city’s “namelessness” as one of its most defining characteristics.
Keywords: Dmitrii Danilov; , Russian literature; Russian provinces; Travelogue and travel writing; Michel de Certeau